Changes in Human Resource Management in the Social Care Sector. An Example of Residential Care Facilities in Łódź - Urbaniak , Bogusława (Studia Oeconomica Posnaniensia, 2016)
The development of care services is accompanied by changes in public management, which affect the way public care establishments, including residential care facilities (RCF), are managed. Changes in the facilities’ HRM are, however, determined by the long-standing model of bureaucratic public management rather than modern HRM. The article analyses selected HRM practices used by the Łódź-based RCF within the organisation of work and selection/development of personnel. An assumption is made that improvements to these practices are mostly conservative in nature, whereas the type of services the facilities render (addressed to dependent persons in need of round-the clock care) makes it more appropriate for them to use HRM specific to knowledge-based organisations, as human capital is a key factor in improving service quality. Based on the results of a questionnaire survey carried out in February and March 2015 among the managers of residential care facilities in Łódź, the scale and direction of the recent changes in their HRM are evaluated.